Radiocarbon Dating the Beginning of the Neolithic in Iberia: New Results, New Problems - Martins, Haidé (2018)
Radiocarbon dating of samples of charred cereal, biomolecularly confirmed sheep bone, human bone from burials, and diagnostic artifacts places the appearance of the ‘Neolithic package’ in Iberia ca. 5500 Cal bc. The earliest dates are statistically indistinguishable from Catalonia to Portugal and, whenever their archaeological context is secure, the associated pottery includes a significant, if not majority cardial-decorated component. These patterns are consistent with models of maritime pioneer colonization whereby the arrival of domesticates results from the dispersal of farming groups carrying the Cardial cultural tradition.